ظاهرة العنف الأسري في الجزائر- دراسة سوسيولوجية - دليلة, خينش (Sciences humaines; Vol. 37 (2014): SCIENCES HUMAINES(Novembre), 2016)
نحاول من خلال هذا المقال التطرق إلى  ظاهرة العنف الأسري في الجزائر ، ومن هم أكثر ضحايا العنف على مستوى الأسرة الجزائرية. و كذا العلاقة بين هذه الظاهرة و الخصائص الاجتماعية و الثقافية للأسرة الجزائرية. لنصل في الأخير إلى نتائج تقلل من حدة الظاهرة و انتشارها.   We  try  through this article to expose the Phenomenon of family violence in algeria and who are the most victims of violence of the algerian family .with The relationship between this phenomenon and the social and cultural characteristics of the Algerian family ; to reach at the end to results that may minimize the severity of this phenomenon and its spread